Cost of care: A study of patients hospitalized for treatment of psychotic illness - P P Rejani; T P Sumesh; K S Shaji (Indian Journal of Psychological Medicine, 2015)
Background: Combination of ill health and poverty poses special challenges to health care providers. Mental illness and costs are linked in terms of long-term treatment and lost productivity, and it affects social development. The purpose of the present study is to assess the economic burden of poor families when a family member needs hospitalization due to psychosis. Materials and Methods: The information was gathered from caregivers of 100 psychotic inpatients of Medical College Hospital of Kerala during a period of 6 months. Data regarding components of expenses such as cost of medicine, laboratory investigations, food, travel, and other miscellaneous expenses during their inpatient period were collected by direct personal interview using specially designed proforma. The data were analyzed using Epi-info software. The patients below the poverty line (BPL) were compared with those above poverty line (APL). Results: There was no significant difference between patients from BPL and APL in respect of amounts spent on the studied variables except for laboratory investigations during the hospital stay. Conclusions: The results showed that the studied subjects are facing financial difficulties not only due to hospitalization, but also due to the recurrent expense of their ongoing medication. The study recommends the need of financial support from the government for the treatment of psychotic patients.